Self-medication for oral health problems in COVID-19 outbreak : prevalence and associated factors = Automedicación para enfermedades orales durante la pandemia del COVID-19 : prevalencia y factores asociados - Alavi Namvar, Mahsa; Mansori, Kamyar; Gerayeli, Mahsa (2022)
This study aimed to investigate self-medication in the COVID-19 outbreak among patients attending the dental clinic of Zanjan University of Medical Sciences. The total number of patients who took part in this research was 306, and they were questioned using a 28-item questionnaire after signing a permission form. SPSS26 was used to gather and analyze the data. There were 196 women and 110 males among the patients.The results showed that the prevalence of self-medication was 53.9%, and a lower educational level was associated with self-medication. The most common problem for self-medicating was toothache, and the most frequent drug was Ibuprofen. The majority of the participants reported that their relatives/friends suggested the drugs to them. The main source of obtaining the drugs was pharmacies. The major reasons for self-medication were the high cost of dental treatments and fear of COVID-19.
Este estudio tuvo como objetivo investigar la automedicación durante la pandemia de COVID-19 entre los pacientes que asisten a la clínica dental de la Universidad de Ciencias Médicas de Zanjan. El número total de pacientes que participaron en esta investigación fue de 306, y fueron interrogados mediante un cuestionario de 28 ítems después de firmar un formulario de autorización. SPSS26 se utilizó para recopilar y analizar los datos. Entre los pacientes había 196 mujeres y 110 varones. Los resultados mostraron que la prevalencia de automedicación fue del 53,9%, y un menor nivel educativo se asoció con la automedicación. El problema más común para la automedicación fue el dolor de "muelas", y el fármaco más frecuente fue el ibuprofeno. La mayoría de los participantes informaron que sus familiares/amigos les sugirieron los medicamentos. La principal fuente de obtención de los medicamentos fueron las farmacias. Las principales razones para la automedicación fueron el alto costo de los tratamientos dentales y el miedo al COVID-19.
En revista Odóvtos, vol. 24, no. 3 (septiembre-diciembre 2022)
Descripción basada en el contenido visto el 05 de diciembre, 2024
También disponible en formato HTML y EPUB